Dispersal From Natal Patch Correlates With the Volatility of Female Sex Pheromones in Parasitoid Wasps - Böttinger, Lea C.; Stökl, Johannes (Frontiers in Ecology and Evolution, 2020)
Chemical communication via pheromones is considered the oldest and most widespread form of communication in nature. However, the way that the enormous diversity of species-specific pheromones evolved is still of debate. One possible process driving pheromone evolution is the mate-finding and dispersal behavior, as long-distance mate-finding requires highly volatile compounds. In contrast, less volatile compounds might be sufficient attractants in species that search for mates within proximity. In the parasitoid wasp genus Leptopilina, the composition of species-specific sex pheromones ranges from highly volatile iridoid compounds through combinations of iridoids with low volatile cuticular hydrocarbons (CHCs) to only CHCs. To study the selective forces shaping the composition of sex pheromones in Leptopilina, we examined the dispersal behavior, i.e. the proportion of male and female wasps dispersing after emergence, in four species with known sex pheromone compositions. If males and females disperse immediately, long-range mate attraction might become necessary, favoring volatile iridoids over CHCs. If mating occurs directly on the host patch, short-range mate attraction by low volatile CHCs might suffice. Our analyses have revealed that the dispersal behavior of Leptopilina males and females after emergence does indeed differ between species with differently volatile sex pheromones. Specifically, males of species with iridoid sex pheromones start to disperse immediately before their females’ emergence, whereas males of species with CHC sex pheromones delay dispersal until their conspecific females emerge. While the differences in female dispersal behavior turned out to be species-specific, differences in male dispersal correlated with the volatility of female-produced sex pheromones of each species. This study significantly contributes to our understanding of the evolution of sex pheromones by differences in dispersal behavior.